Analisis Pengembangan SDM, Pelatihan Kerja dan Kualitas Kerja Terhadap Produktivitas Kerja Karyawan pada PT Bhatini Mitra Jaya di Kabupaten Tangerang Banten - Juniarti Juniarti; Zetary, Luriandra Nadhifa (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to analyze the effect of human resource development, job training, and work quality on employee productivity at PT Bhatini Mitra Jaya in Tangerang Banten district. PT Bhatini Mitra Jaya is a company engaged in service and control valve services and general industrial service services. The approach method used is a quantitative approach with a quantitative descriptive research type. The population of this study were all employees of PT Bhatini Mitra Jaya, totaling 83 employees, while the sampling technique in this study was probability sampling, namely by using census sampling or saturated sampling because the entire population was sampled if the population was below 100. The results of this study indicate that human resource development has a positive and significant effect partially on employee work productivity. employees. Job training has a positive and significant effect partially to employee work productivity. Work quality has a positive and significant effect partially on employee work productivity. In Simultaneously, human resource development, job training and work quality have a positive and significant effect on employee productivity at PT Bhatini Mitra Jaya. The results of this study indicate that partially and simultaneously H1 is accepted and H0 is rejected.